High-energy-density lithium iron phosphate positive electrode material as well as preparation method and application thereof

Through the technological innovation of high-voltage dense fast charging, composite conductive formula and low-added polymer in lithium iron phosphate positive electrode materials, the problem of insufficient application of existing materials in the fast charging field is solved, and a positive electrode material with high energy density and low resistivity is achieved, which improves the fast charging performance and cycle life of the battery.

CN119601589APending Publication Date: 2025-03-11JIANGXI ANCHI NEW ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411712123.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The application of existing lithium iron phosphate positive electrode materials in the fast charging field is limited by the problems of conductivity difference and slow ion diffusion, which leads to poor battery magnification and cycle life, making it difficult to meet the needs of high energy density and fast charging.

Method used

Through three major technological innovations, high-voltage fast charging lithium iron phosphate, composite high-specific table length-to-diameter conducting formula, and low-addition high-bonding polymer, a high-energy density lithium iron phosphate positive electrode material was prepared. The method includes steps such as step doping, spray drying, calcining, sand grinding, and dispersion processes to form a high-pressure and high-loading positive electrode material.

Benefits of technology

The lithium iron phosphate positive electrode material with high energy density, low resistivity and high peel strength is achieved, which improves the fast charging performance and cycle life of the battery, and meets the needs of high energy density and fast charging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601589A_ABST
    Figure CN119601589A_ABST
Patent Text Reader

Abstract

The invention provides a high-energy-density lithium iron phosphate positive electrode slurry and a preparation method and application thereof, and the method comprises the following steps: step doping, mixing and grinding a phosphorus source, a lithium source and an iron source, re-mixing the materials after spray drying and calcining, adding a coating agent, and sanding and calcining to form lithium iron phosphate powder doped with metal ions; adding the lithium iron phosphate powder doped with metal ions, a dispersing agent and a conductive binder into a stirring tank according to a ratio, stirring, dispersing and carrying out dry mixing; adding an organic solvent, stirring and dispersing, stopping the machine, scraping the paddle and the wall, and stirring and dispersing again; vacuumizing, reversing for defoaming, closing the dispersion speed, and stirring to obtain the dispersing agent. The addition amount of the lithium iron phosphate doped with the metal ions is 97%-99%; the addition amount of the conductive adhesive is 0.5%-2.5%; according to the invention, the non-fluorine binder is compounded with the conductive active component to solve the problems of peel strength and pole piece flexibility, and the peel strength of the material is greater than 150N / m under the condition that the addition amount of the binder is less than 1%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion batteries, and in particular to a high energy density lithium iron phosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] In the field of power batteries, both passenger cars and commercial vehicles are increasingly pursuing continuous fast charging, with the aim of solving users' charging anxiety and achieving rapid energy replenishment. Among them, lithium iron phosphate material LFP has accounted for 60% of lithium-ion positive electrode material shipments due to its high cost-effectiveness, high safety and long life. However, LFP's inherent characteristics of poor conductivity and slow ion diffusion have affected its widespread application in the field of fast charging. Therefore, studying LFP positive electrode technology is particularly important for improving battery fast charging performance.

[0003] At present, the fast charging formula of >2C is relatively blank in the field of lithium iron phosphate. The positive electrode technology and preparation of the lithium battery industry often lack in-depth technical analysis of the underlying fast charging principle. For example, the commonly used positive electrode formulas include the following: 1. High addition of carbon black and carbon tubes >2%. Although the resistivity is reduced, it also reduces the compaction and capacity of the pole piece, which is not conducive to improving the energy density; 2. High iron-lithium specific surface area and PVDF >2%. Although it solves the cracking of the pole piece and improves the peeling strength, the internal resistance is high, and the contact internal resistance is increased, the electronic conductivity decreases, and the conductivity of the battery is reduced; 3. In the selection of lithium iron phosphate main materials, although lithium iron phosphate can also achieve 2.50g / cc, the carbon coating is incomplete, the internal resistance and polarization are high, which reduces the rate charging characteristics and the energy conversion efficiency. The above methods are easy to increase the battery impedance, resulting in the deterioration of the battery rate and cycle life, and the low compaction makes it difficult to meet the energy density requirements.

[0004] Therefore, the present invention develops a high energy density lithium iron phosphate positive electrode material and its preparation method and application, which is one of the key technical strategies to achieve fast charging. Summary of the invention

[0005] The present invention provides a high energy density lithium iron phosphate positive electrode material and a preparation method and application thereof, the purpose of which is to solve the above-mentioned problems existing in the background technology.

[0006] In order to achieve the above-mentioned purpose, the embodiments of the present invention provide a high energy density lithium iron phosphate positive electrode slurry and a preparation method and application thereof. The present invention develops a positive electrode high compaction and high loading formula by developing three major technical innovations: high-voltage, dense and fast-charging lithium iron phosphate, a composite high specific aspect ratio conductive formula, and a low-addition high-adhesion polymer.

[0007] An embodiment of the present invention provides a method for preparing a high energy density lithium iron phosphate positive electrode slurry, comprising the following steps:

[0008] S1: doping the phosphorus source, lithium source and iron source stepwise, mixing and grinding, mixing the spray-dried and calcined materials again, adding a coating agent, sand-milling and calcining, and forming lithium iron phosphate powder doped with metal ions;

[0009] S2: adding lithium iron phosphate powder doped with metal ions, dispersant, and conductive binder into a stirring tank in proportion, stirring and dispersing, and dry mixing;

[0010] S3: adding organic solvent, stirring and dispersing, stopping the machine to scrape the wall with a paddle, and stirring and dispersing again;

[0011] S4: Vacuum and reverse to degas, turn off the dispersion speed, stir, and obtain;

[0012] The addition amount of the lithium iron phosphate doped with metal ions is 97% to 99%; the conductive adhesive includes single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, high specific surface carbon black, and fluorine-free adhesive, and the addition amount is 0.5% to 2.5%.

[0013] According to one aspect of an embodiment of the present invention, in step S1, the lithium source is selected from at least any one of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, lithium phosphate, lithium acetate or lithium oxalate; the iron source is selected from at least any one of iron phosphate, iron oxide, ferric pyrophosphate or ferrous oxalate; the phosphorus source is selected from at least any one of phosphoric acid, iron phosphate, ferric pyrophosphate or lithium dihydrogen phosphate; the doped element is selected from at least one of Ti, V, Cr, Mg, Mn, Cu, Al, and the doping amount is ≤8000ppm; the compaction density of the lithium iron phosphate powder doped with metal ions is greater than 2.60g / cc, the powder resistivity is less than 10Ωcm, the primary maximum particle size is less than 2um, and the primary average particle size is 200-400nm.

[0014] According to one aspect of an embodiment of the present invention, step S1 specifically includes the following steps:

[0015] S1.1: Weigh the mixture of iron phosphate, lithium carbonate and tetrabutyl titanate, grind it, spray dry it and calcine it to obtain a mixture 1; the calcination temperature is 600-700°C, the holding time is 10h, the solid content of the sand milling is 30%, and the titanium element doping amount accounts for 100-2000ppm of the finished product;

[0016] S1.2: Weigh the iron phosphate, lithium carbonate and submicron titanium dioxide mixture and grind it, spray dry it and then calcine it to obtain the mixture II; the calcination temperature is 600-750°C, the insulation time is 10h, the solid content of the sand milling is 30%, and the titanium doping amount accounts for 1000-5000ppm of the finished product;

[0017] S1.3: Mix the mixture 1 and the mixture 2 in a ratio of 1:9 to 9:1, add glucose and grind, dry and calcine at a temperature of 700 to 800° C. to obtain the mixture.

[0018] According to one aspect of the embodiment of the present invention, in step S2, the revolution speed is 5 to 35 rpm, the dispersion speed is 100 to 600 rpm, and the dry mixing is performed for 30 to 50 minutes.

[0019] According to one aspect of the embodiment of the present invention, in step S2, the dispersant is at least one of polyvinyl pyrrolidone, polyethers, and polyphosphates, and the addition amount is 0.05% to 0.5%; the conductive binder includes 0.5% to 2% single-walled carbon nanotubes, 4% to 20% multi-walled carbon nanotubes, 4% to 12% graphene, 4% to 28% carbon black, and 20% to 40% fluorine-free binder; the fluorine-free binder is polyacrylonitrile. The conductive component is used to collect current, and the role of the binder is to make the phase between the positive electrode particles and the conductive component uniform and well bonded through van der Waals forces and chemical bonds, and at the same time, a certain adhesion is formed between the positive electrode slurry and the aluminum foil without mechanical peeling.

[0020] According to one aspect of the embodiment of the present invention, the carbon black specific surface is greater than 800m 2 / g, oil absorption value>350mL / 100g; carbon nanotubes 5~20nm, aspect ratio>300; graphene sheet diameter D50<5um, number of layers<5 layers.

[0021] According to one aspect of an embodiment of the present invention, the conductive adhesive is prepared by a homogenizer dispersion process. Compared with the traditional sand milling process, the equipment required is complex, the production efficiency is low, and mechanical grinding easily causes structural fractures of carbon nanotubes, consumes a lot of energy and generates heat, and the long-range conductivity of the conductive agent is greatly reduced, sacrificing many disadvantages of conductivity. The present invention adopts an internal homogenizer dispersion process, and through four-sided uniform air flow grinding, the various complex components of the conductive adhesive can quickly dissolve the irregular agglomeration of each phase under the Brownian motion of high-speed shear of the air flow, forming a composite conductive adhesive high-efficiency additive with uniform dispersion, low liquid viscosity, and complete phase structure, and has the advantages of high solid content and easy dispersion, and is easy to mass produce.

[0022] According to one aspect of an embodiment of the present invention, in step S3, the organic solvent is at least one of N-methylpyrrolidone, dimethyl sulfoxide, and dimethylformamide; the first time: the revolution speed is 15 to 50 rpm and the dispersion speed is 500 to 1000 rpm, and the stirring is for 5 to 10 minutes; the second time: the revolution speed is set to 20 to 50 rpm, the dispersion speed is set to 500 to 1500 rpm, and the stirring is for 30 to 60 minutes.

[0023] According to one aspect of the embodiments of the present invention, in step S4, the vacuum degree is -0.08 to -0.1 MPa, the revolution speed is set to 5 to 20 revolutions per minute, and stirring is performed for 5 to 30 minutes.

[0024] Based on a general inventive concept, an embodiment of the present invention provides a high energy density lithium iron phosphate positive electrode slurry prepared by the above preparation method.

[0025] The embodiments of the present invention also provide the application of the high energy density lithium iron phosphate positive electrode slurry prepared by the above preparation method in lithium ion batteries.

[0026] The prepared positive electrode slurry is baked, uniformly coated on the current collector with a thickness of 1-2 mm, and the solvent is dried to form a positive electrode sheet. Further, it is punched into a specified size and shape to meet the design requirements of the battery.

[0027] The positive electrode sheet, graphite and separator prepared above are stacked and / or wound, packaged in a shell, and dried, injected (electrolyte is injected), packaged, left to stand, formed, and divided to obtain a lithium-ion battery.

[0028] The above scheme of the present invention has the following beneficial effects:

[0029] 1. Compared with the conventional low compaction density lithium iron phosphate material, the present invention innovatively adopts high energy density lithium iron phosphate with a high proportion of 97% to 99% as the base material, which can take into account the requirements of high compaction, high energy efficiency and high power, and then combines a small amount of conductive active ingredients with a conductive binder compounded with polyacrylonitrile, which takes into account high dispersibility, excellent conductivity and high purity, thereby preparing a high energy density lithium iron phosphate positive electrode slurry.

[0030] 2. The new grass iron process composite carbon source of the present invention has high particle size grading, high doping and high crystallinity, compaction>2.60g / cc, 1C greater than 144mAh / g, taking into account the requirements of high compaction, high energy efficiency and high power; the formula also adopts a compound of high specific oil absorption value and aspect ratio carbon black carbon tube, so that the electrode resistivity is less than 5Ωcm; the use of non-fluorine adhesive compound conductive active ingredients to solve the problems of peel strength and electrode flexibility, when the adhesive addition amount is less than 1%, the peel strength of the material is greater than 150N / m.

[0031] 3. The preparation process of the lithium iron phosphate material system of the present invention is mature and has high feasibility for mass production. The preparation process improves the peel strength and conductivity of the material, improves the flexibility and compaction density of the electrode, enhances the fast charging power performance of the material, reduces the material impedance, and extends the battery life. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 It is a SEM picture of the high energy density lithium iron phosphate positive electrode slurry of the present invention. DETAILED DESCRIPTION

[0034] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0035] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0036] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0037] In view of the shortcomings of the commonly used positive electrode formula, an embodiment of the present invention provides a method for preparing a high energy density lithium iron phosphate positive electrode slurry, comprising the following steps:

[0038] S1: doping the phosphorus source, lithium source and iron source stepwise, mixing and grinding, mixing the spray-dried and calcined materials again, adding a coating agent, sand-milling and calcining, and forming lithium iron phosphate powder doped with metal ions;

[0039] S2: adding lithium iron phosphate powder doped with metal ions, dispersant, and conductive binder into a stirring tank in proportion, stirring and dispersing, and dry mixing;

[0040] S3: adding organic solvent, stirring and dispersing, stopping the machine to scrape the wall with a paddle, and stirring and dispersing again;

[0041] S4: Vacuum and reverse to degas, turn off the dispersion speed, stir, and obtain;

[0042] The addition amount of the lithium iron phosphate doped with metal ions is 97% to 99%; the conductive adhesive includes single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, high specific surface carbon black, and fluorine-free adhesive, and the addition amount is 0.5% to 2.5%.

[0043] According to one aspect of an embodiment of the present invention, in step S1, the lithium source is selected from at least any one of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, lithium phosphate, lithium acetate or lithium oxalate; the iron source is selected from at least any one of iron phosphate, iron oxide, ferric pyrophosphate or ferrous oxalate; the phosphorus source is selected from at least any one of phosphoric acid, iron phosphate, ferric pyrophosphate or lithium dihydrogen phosphate; the doped element is selected from at least one of Ti, V, Cr, Mg, Mn, Cu, Al, and the doping amount is ≤8000ppm; the compaction density of the lithium iron phosphate powder doped with metal ions is greater than 2.60g / cc, the powder resistivity is less than 10Ωcm, the primary maximum particle size is less than 2um, and the primary average particle size is 200-400nm.

[0044] According to one aspect of an embodiment of the present invention, step S1 specifically includes the following steps:

[0045] S1.1: Weigh the mixture of iron phosphate, lithium carbonate and tetrabutyl titanate, grind it, spray dry it and calcine it to obtain a mixture 1; the calcination temperature is 600-700°C, the holding time is 10h, the solid content of the sand milling is 30%, and the titanium element doping amount accounts for 100-2000ppm of the finished product;

[0046] S1.2: Weigh the iron phosphate, lithium carbonate and submicron titanium dioxide mixture and grind it, spray dry it and then calcine it to obtain the mixture II; the calcination temperature is 600-750°C, the insulation time is 10h, the solid content of the sand milling is 30%, and the titanium doping amount accounts for 1000-5000ppm of the finished product;

[0047] S1.3: Mix the mixture 1 and the mixture 2 in a ratio of 1:9 to 9:1, add glucose and grind, dry and calcine at a temperature of 700 to 800° C. to obtain the mixture.

[0048] According to one aspect of the embodiment of the present invention, in step S2, the revolution speed is 5 to 35 rpm, the dispersion speed is 100 to 600 rpm, and the dry mixing is performed for 30 to 50 minutes.

[0049] According to one aspect of the embodiment of the present invention, in step S2, the dispersant is at least one of polyvinyl pyrrolidone, polyethers, polyphosphates, and polyacrylates, and the addition amount is 0.05% to 0.5%; the conductive binder includes 0.5% to 2% single-walled carbon nanotubes, 4% to 20% multi-walled carbon nanotubes, 4% to 12% graphene, 4% to 28% carbon black, and 20% to 40% fluorine-free binder; the fluorine-free binder is polyacrylonitrile. The conductive component is used to collect current, and the role of the binder is to make the phase between the positive electrode particles and the conductive component uniform and well bonded through van der Waals forces and chemical bonds, and at the same time, a certain adhesion is formed between the positive electrode slurry and the aluminum foil without mechanical peeling.

[0050] According to one aspect of the embodiment of the present invention, the carbon black specific surface is greater than 800m 2 / g, oil absorption value>350mL / 100g; carbon nanotubes 5~20nm, aspect ratio>300; graphene sheet diameter D50<5um, number of layers<5 layers.

[0051] According to one aspect of an embodiment of the present invention, the conductive adhesive is prepared by a homogenizer dispersion process. Compared with the traditional sand milling process, the equipment required is complex, the production efficiency is low, and mechanical grinding easily causes structural fractures of carbon nanotubes, consumes a lot of energy and generates heat, and the long-range conductivity of the conductive agent is greatly reduced, sacrificing many disadvantages of conductivity. The present invention adopts an internal homogenizer dispersion process, and through four-sided uniform air flow grinding, the various complex components of the conductive adhesive can quickly dissolve the irregular agglomeration of each phase under the Brownian motion of high-speed shear of the air flow, forming a composite conductive adhesive high-efficiency additive with uniform dispersion, low liquid viscosity, and complete phase structure, and has the advantages of high solid content and easy dispersion, and is easy to mass produce.

[0052] According to one aspect of an embodiment of the present invention, in step S3, the organic solvent is at least one of N-methylpyrrolidone, dimethyl sulfoxide, and dimethylformamide; the first time: the revolution speed is 15 to 50 rpm and the dispersion speed is 500 to 1000 rpm, and the stirring is for 5 to 10 minutes; the second time: the revolution speed is set to 20 to 50 rpm, the dispersion speed is set to 500 to 1500 rpm, and the stirring is for 30 to 60 minutes.

[0053] According to one aspect of the embodiments of the present invention, in step S4, the vacuum degree is -0.08 to -0.1 MPa, the revolution speed is set to 5 to 20 revolutions per minute, and stirring is performed for 5 to 30 minutes.

[0054] Based on a general inventive concept, an embodiment of the present invention provides a high energy density lithium iron phosphate positive electrode slurry prepared by the above preparation method.

[0055] The embodiments of the present invention also provide the application of the high energy density lithium iron phosphate positive electrode slurry prepared by the above preparation method in lithium ion batteries.

[0056] The prepared positive electrode slurry is baked, uniformly coated on the current collector with a thickness of 1-2 mm, and the solvent is dried to form a positive electrode sheet. Further, it is punched into a specified size and shape to meet the design requirements of the battery.

[0057] The positive electrode sheet, graphite and separator prepared above are stacked and / or wound, packaged in a shell, and dried, injected (electrolyte is injected), packaged, left to stand, formed, and divided to obtain a lithium-ion battery.

[0058] The following will describe the invention through specific embodiments.

[0059] Example 1

[0060] This embodiment provides a method for preparing a high energy density lithium iron phosphate positive electrode slurry.

[0061] The method of this embodiment specifically includes the following steps:

[0062] (1) Preparation of Ti-doped 2+ Lithium iron phosphate powder

[0063] A. Weigh the iron phosphate, lithium carbonate and tetrabutyl titanate mixture and grind it to a solid content of 30% and a titanium doping amount of 2000ppm in the finished product. Spray dry the ground material and calcine it at a calcination temperature of 730°C for 10 hours to obtain a mixture 1.

[0064] B. Weigh the iron phosphate, lithium carbonate and submicron titanium dioxide mixture and sand grind it. The solid content of sand grinding is 30%, and the titanium doping content accounts for 4000ppm of the finished product. The sand grinding material is spray dried and calcined at 780℃ for 10h to obtain the mixture II.

[0065] C. Mix the mixture 1 and the mixture 2 in the ratio of 8:2, add glucose, sand-grind and dry, then calcine at a sintering temperature of 750°C to obtain Ti-doped 2+ Lithium iron phosphate powder;

[0066] (2) 98.2% doped with Ti 2+ Add lithium iron phosphate powder, 0.3% polyacrylate polyether dispersant, and 1.5% conductive binder into a stirring tank and stir and disperse them. The revolution speed is 5 rpm, the dispersion speed is 100 rpm, and the dry mixing is performed for 30 minutes.

[0067] The conductive binder includes 2% single-walled carbon nanotubes, 18% multi-walled carbon nanotubes, 12% graphene, 28% carbon black, and 40% polyacrylonitrile, which are prepared by a homogenizer dispersion process; further, the carbon black ratio is 900m 2 / g, oil absorption value is 450mL / 100g; carbon nanotubes are 5nm, aspect ratio is 350; graphene sheet diameter D50 is 3um, number of layers is 3; dispersion working frequency is 40-60Hz, time is 50min;

[0068] (3) Add N-methylpyrrolidone, stir and disperse, stop the machine to scrape the wall with a paddle, and stir and disperse again; wherein, when the revolution speed is 15 rpm and the dispersion speed is 500 rpm, stir for 5 minutes; the second time: the revolution speed is set to 20 rpm, the dispersion speed is set to 500 rpm, and stir for 30 minutes;

[0069] (4) Vacuum and reverse to degas, turn off the dispersion speed, and stir to obtain the product; wherein the vacuum degree is -0.08 MPa, the revolution speed is set to 5 revolutions per minute; and stir for 5 minutes.

[0070] The preparation process of the pole piece includes the following steps:

[0071] Coating slurry: The prepared positive electrode slurry is evenly coated on the aluminum foil to form a coating. This step requires controlling the coating thickness and is usually completed using a special coating machine.

[0072] Drying: After coating, the aluminum foil coated with the slurry is placed in a drying device and dried at a certain temperature to remove the solvent in the slurry and solidify the slurry on the aluminum foil.

[0073] Rolling process: In order to ensure that the thickness and density of the pole piece meet the requirements, rolling process is required. A special roller press is used to compact the pole piece to achieve the required thickness and density.

[0074] Cutting and assembly: The rolled electrode sheets are cut into the required size and shape, and then assembled into battery cells together with separators, electrolytes and other components.

[0075] Example 2

[0076] This embodiment is based on the preparation method of embodiment 1, except that the main material of this embodiment is 97.2% lithium iron phosphate, the conductive binder is 2.5%, and the other parameters and steps are the same as those of embodiment 1.

[0077] Example 3

[0078] This embodiment is based on the preparation method of embodiment 1, except that the main material of this embodiment is 98.7% lithium iron phosphate, the conductive binder is 1.0%, and the other parameters and steps are the same as those of embodiment 1.

[0079] Comparative Example 1

[0080] This comparative example is based on the preparation method of Example 1, except that 95.2% of the lithium iron phosphate main material (PC20) is synthesized by conventional solid phase method, 2% super-Li carbon black and 0.5% multi-walled carbon tubes are used as the conductive agent, 2.0% of domestically produced PVDF produced by emulsion polymerization is used as the binder, and 0.3% conventional PVP is used as the dispersant. Other parameters and steps are the same as those in Example 1.

[0081] Comparative Example 2

[0082] This comparative example is based on the preparation method of Example 1, except that the main material is 96.2% lithium iron phosphate, the conductive agent uses 0.5% super-Li carbon black and 1% multi-walled carbon tubes, the binder uses 2.0% domestically produced PVDF polymerized by emulsion polymerization and 0.3% dispersant PVP, and the other parameters and steps are the same as those in Example 1.

[0083] Comparative Example 3

[0084] This comparative example is based on the preparation method of Example 1, except that the main material is 95.7% lithium iron phosphate, the conductive agent is 2% super-Li carbon black, the binder is 2.0% suspension copolymer PVDF Solvay 5130, and the alcohol-amine dispersant is 0.3%. Other parameters and steps are the same as those in Example 1.

[0085] The performance test results of the pole pieces prepared in the above embodiments and comparative examples and applied in batteries are shown in Table 1 below.

[0086] Table 1

[0087]

[0088] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high energy density lithium iron phosphate positive electrode slurry, characterized in that: The steps include: S1: doping the phosphorus source, lithium source and iron source stepwise, mixing and grinding, mixing the spray-dried and calcined materials again, adding a coating agent, sand-milling and calcining, and forming lithium iron phosphate powder doped with metal ions; S2: adding lithium iron phosphate powder doped with metal ions, dispersant, and conductive binder into a stirring tank in proportion, stirring and dispersing, and dry mixing; S3: adding organic solvent, stirring and dispersing, stopping the machine to scrape the wall with a paddle, and stirring and dispersing again; S4: Vacuum and reverse to degas, turn off the dispersion speed, stir, and obtain; The addition amount of the lithium iron phosphate doped with metal ions is 97% to 99%; the conductive adhesive includes single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, high specific surface carbon black, and fluorine-free adhesive, and the addition amount is 0.5% to 2.5%.

2. The method for preparing a high energy density lithium iron phosphate positive electrode slurry according to claim 1, characterized in that: Step S1, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, lithium phosphate, lithium acetate or lithium oxalate; the iron source is selected from at least one of iron phosphate, iron oxide, ferric pyrophosphate or ferrous oxalate; the phosphorus source is selected from at least one of phosphoric acid, iron phosphate, ferric pyrophosphate or lithium dihydrogen phosphate; the doped element is selected from at least one of Ti, V, Cr, Mg, Mn, Cu, Al, and the doping amount is ≤8000ppm; the compaction density of lithium iron phosphate powder doped with metal ions is greater than 2.60g / cc, the powder resistivity is less than 10Ωcm, the primary maximum particle size is less than 2um, and the primary average particle size is 200-400nm.

3. The method for preparing a high energy density lithium iron phosphate positive electrode slurry according to claim 1, characterized in that: Step S1 specifically includes the following steps: S1.1: Weigh the mixture of iron phosphate, lithium carbonate and tetrabutyl titanate, grind it, spray dry it and calcine it to obtain a mixture 1; the calcination temperature is 600-700°C, the holding time is 10h, the solid content of the sand milling is 30%, and the titanium element doping amount accounts for 100-2000ppm of the finished product; S1.2: Weigh the iron phosphate, lithium carbonate and submicron titanium dioxide mixture and grind it, spray dry it and then calcine it to obtain the mixture II; the calcination temperature is 600-750°C, the insulation time is 10h, the solid content of the sand milling is 30%, and the titanium doping amount accounts for 1000-5000ppm of the finished product; S1.3: Mix the mixture 1 and the mixture 2 in a ratio of 1:9 to 9:1, add glucose and grind, spray dry and calcine at a temperature of 700 to 800° C. to obtain the mixture.

4. The method for preparing a high energy density lithium iron phosphate positive electrode slurry according to claim 1, characterized in that: Step S2, the revolution speed is 5 to 35 rpm, the dispersion speed is 100 to 600 rpm, and the dry mixing is performed for 30 to 50 minutes; the dispersant is at least one of polyvinyl pyrrolidone, polyethers, and polyphosphates, and the addition amount is 0.05% to 0.5%; the conductive adhesive includes 0.5% to 2% single-walled carbon nanotubes, 4% to 20% multi-walled carbon nanotubes, 4% to 12% graphene, 4% to 28% carbon black, and 20% to 40% fluorine-free adhesive; the fluorine-free adhesive is polyacrylonitrile.

5. The method for preparing a high energy density lithium iron phosphate positive electrode slurry according to claim 4, characterized in that: The carbon black ratio is > 800m 2 / g, oil absorption value>350mL / 100g; carbon nanotubes 5~20nm, aspect ratio>300; graphene sheet diameter D50<5um, number of layers<5 layers.

6. The method for preparing a high energy density lithium iron phosphate positive electrode slurry according to claim 4 or 5, characterized in that: The conductive adhesive is prepared by a homogenizer dispersion process.

7. The method for preparing a high energy density lithium iron phosphate positive electrode slurry according to claim 1, characterized in that: Step S3, the organic solvent is at least one of N-methylpyrrolidone, dimethyl sulfoxide, and dimethylformamide; First time: Stir for 5 to 10 minutes at a revolution speed of 15 to 50 rpm and a dispersion speed of 500 to 1000 rpm; Second time: the revolution speed is set to 20-50 rpm, the dispersion speed is set to 500-1500 rpm, and stirring is performed for 30-60 minutes.

8. The method for preparing a high energy density lithium iron phosphate positive electrode slurry according to claim 1, characterized in that: Step S4, the vacuum degree is -0.08 to -0.1 MPa, the revolution speed is set to 5 to 20 rpm; stirring is performed for 5 to 30 minutes. 9 . The high energy density lithium iron phosphate positive electrode slurry prepared by the preparation method according to claim 1 .

10. Use of the high energy density lithium iron phosphate positive electrode slurry prepared by the preparation method according to any one of claims 1 to 8 in lithium ion batteries.

Citation Information

Cited By

  • Lithium iron phosphate material and preparation method thereof, positive pole piece and secondary battery

    CN120757092A